Technical note: Photosensitisation jaundice syndrome in West African Dwarf sheep and goats grazed on Brachiaria decumbens - Opasina, B.A. (1985)
In a dry season grazing trial with Brachiaria decumbens cv. Basilisk at Ibadan in southwest Nigeria, 14 from a group of 36 West African Dwarf sheep, and 1 from a group of 16 goats, died. The main clinical and post-mortem findings were signs of photosensitisation and jaundice. Further investigation of the effect of the grass on ruminant production in Nigeria would be required.